Predictive models in the diagnosis and treatment of autoimmune epilepsy. (26th May 2017) - Dubey, Divyanshu; Singh, Jaysingh; Britton, Jeffrey W.; Pittock, Sean J.; Flanagan, Eoin P.; Lennon, Vanda A.; Tillema, Jan‐Mendelt; Wirrell, Elaine; Shin, Cheolsu; So, Elson; Cascino, Gregory D.; Wingerchuk, Dean M.; et al.
Summary: Objective: To validate predictive models for neural antibody positivity and immunotherapy response in epilepsy. Methods: We conducted a retrospective study of epilepsy cases at Mayo Clinic (Rochester‐MN; Scottsdale‐AZ, and Jacksonville‐FL) in whom autoimmune encephalopathy/epilepsy/dementia autoantibody testing profiles were requested (06/30/2014‐06/30/2016). An Antibody Prevalence in Epilepsy (APE) score, based on clinical characteristics, was assigned to each patient. Among patients who received immunotherapy, a Response to Immunotherapy in Epilepsy (RITE) score was assigned. Favorable seizure outcome was defined as >50% reduction of seizure frequency at the first follow‐up. Results: Serum and cerebrospinal fluid (CSF) from 1, 736 patients were sent to the Mayo Clinic Neuroimmunology Laboratory for neural autoantibody evaluation. Three hundred eighty‐seven of these patients met the diagnostic criteria for epilepsy. Central nervous system (CNS)–specific antibodies were detected in 44 patients. Certain clinical features such as new‐onset epilepsy, autonomic dysfunction, viral prodrome, faciobrachial dystonic seizures/oral dyskinesia, inflammatory CSF profile, and mesial temporal magnetic resonance imaging (MRI) abnormalities had a significant association with positive antibody results. A significantly higher proportion of antibody‐positive patients had an APE score ≥4 (97.7% vs. 21.6%, p < 0.01). Sensitivity and specificity of an APE score ≥4 to predict presence of specific neural auto‐antibody were 97.7% and 77.9%, respectively. In the subset of patients who received immunotherapy (77), autonomic dysfunction, faciobrachial dystonic seizures/oral dyskinesia, early initiation of immunotherapy, and presence of antibodies targeting plasma membrane proteins (cell‐surface antigens) were associated with favorable seizure outcome. Sensitivity and specificity of a RITE score ≥7 to predict favorable seizure outcome were 87.5% and 83.8%, respectively. Significance: APE and RITE scores can aid diagnosis, treatment, and prognostication of autoimmune epilepsy. A PowerPoint slide summarizing this article is available for download in the Supporting Information sectionhere .